A1.25 Visualisation and characterisation of citrullinated antigen-specific B cells from peripheral blood of patients with rheumatoid arthritis. (13th February 2015) - Kerkman, PF; Fabre, E; van der Voort, EH; Germar, KL; Baeten, DL; Huizinga, TWJ; Toes, REM; Scherer, HU
Abstract : Background and objectives: In Rheumatoid arthritis (RA), anti-citrullinated protein antibodies (ACPA) represent highly disease-specific biomarkers found in the majority of patients. As ACPA have been implicated in disease pathogenesis, it is of crucial relevance to understand the underlying B cell response. In this context, visualisation of citrullinated antigen-specific B cells would allow for a detailed characterisation of the immune response to better understand its development and maintenance. Unfortunately, visualisation of autoreactive B cells in humans has proven extremely difficult. Materials and methods: Using the CCP2-antigen and its arginine control variant, we developed a multicolour tetramer-based staining method to visualise citrullinated antigen-specific B cells in peripheral blood of RA patients by flow-cytometry. Specificity of the staining was verified by culturing tetramer-positive and -negative B cells isolated by FACS. Citrullinated antigen-reactive B cells were further phenotyped using cell surface markers associated with developmental and functional B cell characteristics. Finally, the frequency of citrullinated antigen-reactive B cells was correlated to ACPA serum levels and in vitro ACPA production. Results: The staining procedure successfully separated citrullinated antigen-reactive B cells from non-specific background signals. Already fourteen FACS-sorted tetramer-positive B cells produced detectable amounts of ACPA, whereas no ACPA production was observed in cultures of up to 5000 tetramer-negative B cells. The majority of citrullinated antigen-reactive B cells had a post-germinal centre memory or plasmablast phenotype. Up to 1 in 200 memory B cells were directed against citrullinated antigens, and their frequency correlated with spontaneous ACPA production in culture and ACPA serum titres in vivo . Conclusions: We show, for the first time, the specific and reliable identification of citrullinated antigen-specific B cells in high frequencies in peripheral blood of RA patients. The majority of this population has a memory phenotype and closely reflects the dynamics of the in vivo ACPA response. These data provide the basis for a detailed characterisation of this disease-specific immune response on a single cell level and could lead to the identification of novel therapeutic targets.